2018
DOI: 10.21276/ijcmr.2018.5.4.22
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Osteoporosis among Post Menopausal Women

Abstract: Introduction:Osteoporosis amongst post-menopausal females is regarded as a important public health matter associated with significant socioeconomic burden and morbidity. It is generally divided into primary type and secondary type depending upon its underlying causation. The present study was conducted with the aim to determine the risk factors of osteoporosis amongst postmenopausal women reporting to the Hospital. Material and methods:The present cross sectional survey was conducted amongst 270 post-menopausa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…[ 3 ] Postmenopausal osteoporosis risk factors vary from region to region and are well documented in Caucasians and Asian women. [ 3 7 26 27 28 29 30 31 ] The risk factors in African-American women are similar to those of their white counterparts. [ 28 ] However, there is a paucity of data on risk factors for postmenopausal osteoporosis in African women whose lifestyle and environmental factors are different from western subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 3 ] Postmenopausal osteoporosis risk factors vary from region to region and are well documented in Caucasians and Asian women. [ 3 7 26 27 28 29 30 31 ] The risk factors in African-American women are similar to those of their white counterparts. [ 28 ] However, there is a paucity of data on risk factors for postmenopausal osteoporosis in African women whose lifestyle and environmental factors are different from western subjects.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] The prevalence and impact of osteoporosis among different nations vary due to population variations and differences in the availability of resources. [ 7 ] The single most important manifestation of postmenopausal osteoporosis is a fracture, usually of the hip. [ 8 ] There is increased mortality of 12–20% during the two years following a hip fracture and more than 50% of survivors are unable to return to independent living.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by low bone mass, deterioration of bone tissue and disruption of bone architecture, compromised bone strength, and an increase in the risk of fracture [23,21] Osteoporosis medications include bisphosphonates, receptor activator of nuclear factor kappa-B ligand inhibitors, estrogen agonists/antagonists, parathyroid hormone analogs, and calcitonin [22]. Bisphosphonates are a synthetic class of pyrophosphate analogs that are powerful inhibitors of bone resorption which are commonly used as a medication for the prevention and therapy of osteoporosis and osteopenia, also used to treat tumor diseases [24].…”
Section: Fig 3 Showing the Distribution Of Participants Based On Their Awareness About Prevention Of Bone Loss Or Bone Pain By Taking Calmentioning
confidence: 99%
“…Secondary osteoporosis refers to bone loss that ensues as a secondary effect of other diseases or drug treatment. 1,2 It is reported that 42.5% women and 24.6% men above the age of 50 years suffer from osteoporosis. The rates of osteoporotic fracture in India are among the highest in Asia.…”
Section: Introductionmentioning
confidence: 99%